A Transformation of Back-Office System from MVC to Blazor and Secure Password Using PBKDF2 - Mustaffa Kamal, Mohamad Aizuddin; Chuah Chai Wen (Applied Information Technology And Computer Science, 2022)
DIY Tour Asia is an online booking company for package tours founded in 2012. DIY Tour Asia online platform has two different web applications. They are customer application and Back-Office System. The customer application allows customers to view and book available package tours. The Back-Office System allows administrators and staffs to manage the business in term of inventory, price, availability, and reporting. DIY Tour Asia Back-Office System is using the Model-View-Controller (MVC) framework as their backbone. MVC framework is causing a lot of code duplicates and is tightly coupled. Migrating to the Blazor framework can reduce code duplication through the Dependency Injection (DI) method. In addition, the system uses PBKDF2 to strengthen password security from brute force attacks. The PBKDF2 algorithm hashes the password before storing it in the database. The Object-Oriented Software Development is chosen for the methodology. The proposed system is developed using C# language. The developed system allowed only staff members to log in to the system. After login to the system, the user may choose to interact with any of the five modules which are administration, profile management, hotel, hotel booking, and hotel sales report. However, the administration module is only for administrators. The administration, profile management and hotel modules support CRUD process. The authorized user may view details of hotel booking and cancel them. The hotel sales report module allows user to export the results in three formats which are Microsoft Word, Microsoft Excel, and Portable Document Format